2020
DOI: 10.1364/josab.399048
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional ultrabroadband and wide-angle absorption in graphene-embedded photonic crystals with the cascading structure comprising the Octonacci sequence

Abstract: Using the transfer matrix method, a unidirectional absorber with an ultrabroadband absorption bandwidth and angular stability is realized in the graphene-embedded photonic crystals (GPCs) arranged by the cascading structure formed with the periodic sequence and the quasi-periodic Octonacci sequence in the terahertz regime. As a result, the surface conductivity of the graphene sheet can be modulated via the chemical potential, and the characteristics of the proposed absorber are tunable. Compared to the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Photonic crystals (PCs) have received a lot of interest since their invention because of their ability to control light propagation 1 3 . One key characteristic of PCs is the photonic bandgap (PBG) which prevents light propagation in its waveband 4 , 5 . Because of their unique features, PCs are utilized to create optical devices such as reflectors 6 8 , lasers 9 , 10 , fibers 11 , 12 , and tunable optoelectronic devices 13 – 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Photonic crystals (PCs) have received a lot of interest since their invention because of their ability to control light propagation 1 3 . One key characteristic of PCs is the photonic bandgap (PBG) which prevents light propagation in its waveband 4 , 5 . Because of their unique features, PCs are utilized to create optical devices such as reflectors 6 8 , lasers 9 , 10 , fibers 11 , 12 , and tunable optoelectronic devices 13 – 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer structures have attracted significant attention in the past few years because of the advantages of simple structures and enhanced absorption. [37][38][39][40][41][42][43] It has been demonstrated that most previous studies into structures have focused on narrowband absorption. [44][45][46][47] Recently, Xie et al proposed a stacked Fabry-Perot (FP) multilayer structure for spacecraft thermal control that achieves a highly enhanced infrared emittance as well as emittance tunability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing number of studies in the field of nonlocal metamaterials, the effect of spatial dispersion on optical properties of photonic hypercrystals has not been yet discussed. Photonic hypercrystals (PHCs) are a novel class of metamaterials combining properties of photonic crystals and hyperbolic media [ 20 ] and revealing interesting properties, such as difractionless imaging [ 21 ], optical bistability [ 22 ], cloaking [ 23 ], or tunable broadband unidirectional absorption [ 24 ]. Recently, it has also been demonstrated that tunable lasing with voltage-controllable single mode generation is also possible in this class of structure [ 25 ].…”
Section: Introductionmentioning
confidence: 99%